Integration of Design Sprint Method into Mobile Development Application Life Cycle to Create MobilePQI Application Prototype - Fenty Eka Muzayyana Agustin; Nuriyah Thahir; Ade Rina Farida; Kania Mayastika (JURNAL TEKNIK INFORMATIKA, 2024)
This study aims to create a mobile-based learning application that can be used to support blended learning. Blended Learning is carried out synchronously, either online using Zoom or Google Meet, or offline in the classroom. asynchronous learning is implemented using MobilePQI Apps. MobilePQI Apps was developed using the Kotlin programming tool and  MADLC methodology (Mobile Application Development Life Cycle). MADLC consists of seven stages: Identification; Design; Development; Prototyping; Testing; Deployment; and Maintenance. We use design sprint method and figma to create design prototype, and Kotlin development kit. The testing method used heuristics evaluation which tests 10 usability principles. The number of questions asked was 115, with 5 respondents consisting of 3 students and 3 lecturers. The results of the heuristics evaluation score were 89% of respondents answered YES. That it can be concluded that the 10 usability  principles of the prototype was acceptable. The SUS results show a score of 74, which means the application's user interface is in the Good and acceptable category.